Growth and Production of Two Varieties Soybean (Glycine soja L.) Response on Applicating of Organic Liquid Fertilizer - Chairum Vika; T Irmansyah; Jonatan Ginting (Jurnal Agroekoteknologi, 2018)
The objective of the research is know the response of growth and production of two varieties soybean on applicating of Organic Liquid Fertilizer. The research was conducted in UPT Balai Benih Induk (BBI) Palawija Tanjung Selamat, Kecamatan Medan Sunggal, Kabupaten Deli Serdang Medan, started from Juny until September 2016,  used factorial randomized block design with 2 factors. The first factor is varieties (Cikuray, Detam-2) and the second factor is Applicating of Organic Liquid Fertilizer (Control, Rabbit’s urine, Cow’s urine, Goat’s urine ). The result of this reseach showed that varieties were significantly effect to plant height 2, 3 and 6 week after planting (WAP), root dry weight, the number of pods fullness per plant, the number of pods empty per plant, dry weight of 100 seeds, dry weight of seeds per plant, dry weight of seeds per plots. Application organic liquid fertilizer were not significantly effected all parameters. Interaction of varieties and application of Organic Liquid Fertilizer were not effected all parameters. Dry weight of seeds per plant and dry weight of seeds per plots highly at Cikuray (V1).The objective of the research is know  the response of growth and production of two varieties soybean on applicating of Organic Liquid Fertilizer. The research was conducted in UPT Balai Benih Induk (BBI) Palawija Tanjung Selamat, Kecamatan Medan Sunggal, Kabupaten Deli Serdang Medan, started from Juny until September 2016,  used factorial randomized block design with 2 factors. The first factor is varieties (Cikuray, Detam-2) and the second factor is Applicating of Organic Liquid Fertilizer (Control, Rabbit’s urine, Cow’s urine, Goat’s urine ). The result of this reseach showed that varieties were significantly effect to plant height 2, 3 and 6 week after planting (WAP), root dry weight, the number of pods fullness per plant, the number of pods empty per plant, dry weight of 100 seeds, dry weight of seeds per plant, dry weight of seeds per plots. Application organic liquid fertilizer were not significantly effected all parameters. Interaction of varieties and application of Organic Liquid Fertilizer were not effected all parameters. Dry weight of seeds per plant and dry weight of seeds per plots highly at Cikuray (V1).